O duplo no romantismo: o exemplo de E.T.A. Hoffmann - Guimarães, Ana Rosa Gonçalves de Paula (2017)
This study aims to point out causes and ways in which the phenomenon of double becomes one of the symbols of German Romanticism. In order to do so, the historical-social context between the end of the eighteenth century and the mid-nineteenth century was revisited in order to discuss the particularities of the panorama in which the subject was permeated, and it is possible to notice that the outbreak of social crisis also reverberated for the conflicting existence of the subject with his "selves", that is, with its fragmentations and divisions. The main characteristics of this artistic movement allowed to understand what the romantic man sought and felt. Thus, some of the interfaces of Romanticism with psychoanalysis aimed to consider the psychic antagonisms as well as the apprehension of the manifestations of the nocturnal side of the human soul, the aspects of the unconscious and the fragmentation of the subject, making it a "divided": a part of his being is conscious and the other part, conscious, preoccupations that anticipated psychoanalysis. The manifestations of the double in the literature of the German Romanticism had as a highlight the writer E. T. A. Hoffmann. And through the interpretative reading of his tales: The lost image, Doctor Trabacchio and The Doubles, have been traversed the natures for the manifestations of such phenomenon, which oscillated both for the non-recognition of self, and for the utopian necessity of the romantic subject's reunion with himself. The manifestations of the double thus evidence the romantic need to perceive it as pertinent to the "real and true self", as ambition for the principle of the absolute. Hoffmann, however, develops in his fiction that the subject is a self in itself and fragmented in itself - "divided" which makes of its existence the perpetual conflict of being, which seeks the understanding of a unity tied to the concerning its origin and its essence. From this, there is the possibility of the encounter with the double, as the "other self" or as the "other selves", in order to have the permanent construction of the subject and the eternal search for its social and psychic fragments. Even with the possibility of observing a "particular form of unity," it divides itself. Symbolically, life can be a literary creation, which offers man, even though he is "divided" the opportunity for him to be a writer of himself.